Brain activity during walking: A systematic review. (October 2015) - Hamacher, Dennis; Herold, Fabian; Wiegel, Patrick; Hamacher, Daniel; Schega, Lutz
Abstract: Background: This systematic review provides an overview of the literature deducing information about brain activation during (1) imagined walking using MRI/fMRI or (2) during real walking using measurement systems as fNIRS, EEG and PET. Methods: Three independent reviewers undertook an electronic database research browsing six databases. The search request consisted of three search fields. The first field comprised common methods to evaluate brain activity. The second search field comprised synonyms for brain responses to movements. The third search field comprised synonyms for walking. Results: 48 of an initial yield of 1832 papers were reviewed. We found differences in cortical activity regarding young vs. old individuals, physically fit vs. physically unfit cohorts, healthy people vs. patients with neurological diseases, and between simple and complex walking tasks. Conclusions: We summarize that the dimension of brain activity in different brain areas during walking is highly sensitive to task complexity, age and pathologies supporting previous assumptions underpinning the significance of cortical control. Many compensation mechanisms reflect the brain's plasticity which ensures stable walking.